2020
DOI: 10.1177/0269216320956819
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in palliative care research: What works, and why? A qualitative evaluation

Abstract: Background: Public involvement is increasingly considered a prerequisite for high-quality research. However, involvement in palliative care is impeded by limited evidence on the best approaches for populations affected by life-limiting illness. Aim: To evaluate a strategy for public involvement in palliative care and rehabilitation research, to identify successful approaches and areas for improvement. Design: Co-produced qualitative evaluation using focus groups and interviews. Thematic analysis undertaken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…11 It has been suggested that this may be because common approaches to public involvement adopted in primary data research are not appropriate within big data analysis studies. 12,13 While public members are commonly involved in primary research to review and develop patient information leaflets or other research materials, undertake interviews with research participants or even support recruitment for a clinical trial, these involvement opportunities are not applicable to big data research. 13,14 In addition, the highly data driven discussions that underline this type of research can present a barrier to public involvement with 'unfamiliar' and 'scientific' language repeatedly being cited as an obstacle, across fields.…”
Section: Opportunities For Public Involvement In Big Data Research In Palliative and End-oflife Carementioning
confidence: 99%
“…11 It has been suggested that this may be because common approaches to public involvement adopted in primary data research are not appropriate within big data analysis studies. 12,13 While public members are commonly involved in primary research to review and develop patient information leaflets or other research materials, undertake interviews with research participants or even support recruitment for a clinical trial, these involvement opportunities are not applicable to big data research. 13,14 In addition, the highly data driven discussions that underline this type of research can present a barrier to public involvement with 'unfamiliar' and 'scientific' language repeatedly being cited as an obstacle, across fields.…”
Section: Opportunities For Public Involvement In Big Data Research In Palliative and End-oflife Carementioning
confidence: 99%
“…Unfortunately, there is a reluctance to involve palliative care patients in such research, perhaps due to a lack of confidence about appropriate approaches for this group. 29 Given the challenges of a life-limiting illness, it may seem unnecessary and impractical to move beyond such initiatives as the palliative and end of life care priority setting partnership, which included patients in identifying and prioritizing gaps in current research evidence. 30 Indeed, palliative care patients are often seen as too sick and having too little energy to contribute meaningfully to more active research practices.…”
Section: Patient and Public Involvement In Research (Ppi)mentioning
confidence: 99%
“…Various tools have been developed to help support PPI in research; a 2019 systematic review identified and classified 64 frameworks ( 47 ), these were rarely adopted outside the research groups that developed them, showing how a one-size-fits all approach to PPI guidance may not work. While a number of existing frameworks may be used to help inform PPI in psychedelic research ( 8 , 48 50 ), none of these account for the unique position which this field of research finds itself, namely: a highly complex socio-political landscape; rapidly changing drug policy; a wealth of knowledge stemming from a long tradition of psychedelic use pre-dating modern research; an underrepresentation of women, Black, Asian, and ethnically diverse populations; the social stigma associated with recreational use; and the 20-year hiatus in psychedelic research. All of these factors are not only important considerations for researchers conducting studies, but also for those taking part, particularly considering the potential for long-term impact on a participant's life ( 51 ).…”
Section: Introductionmentioning
confidence: 99%